Na trilha do PROUNI: implantação, acompanhamento e perspectivas em uma instituição de ensino superior de Santa Catarina - Krames, Ilisabet Pradi (2010)
This paper is about the Programa Universidade para Todos PROUNI, a current theme that has been gaining attention on research into the field of Brazilian Higher Education. This public education policy is aimed at democratizing Higher Education in the country, and is a reference to this work, which aims to analyze PROUNI implantation and its repercussions in an Institute of Higher Education in Santa Catarina. The methodological option used had been based on the qualitative approach, giving priority to the analysis of the content. The application of the research tools with the students benefited from a PROUNI scholarship and with the three segments of the Institute of Higher Education manager group researched allowed the crossing of the categories that made up axis of analysis. This procedure allowed us to determine the closeness and antagonism degree between the perceptions and expectations of the students and the social commitment policy of the Institute that admitted and hosted the student that has been benefited with the scholarship. This policy has been understood in the context of this research as a differentiator in terms of social responsibility that optimizes the permanence of the student in Higher Education. When investigating the process of deploying PROUNI and its repercussions in the Institute, the research shows: expectations and social commitments of the Higher Education Institute resulting from the implantation of the program; expectations and commitment of the students; the students point of view about the access and retention in the Higher Education Program; the understanding about PROUNI as a social inclusion policy, and the differential of a private institute that admits and hosts the students that have been benefited with the program scholarship. The research and data analysis methodologies pointed out that the Public Policies and the actions of the State aimed at inclusion and social welfare can achieve the results they aim, if there is a collective involvement of the Institutes of Higher Education that join PROUNI; for the students of the Institute of Higher Education that are connected to the program, we realized that the access can be understood as the unique opportunity to change his/her live and, despite difficulties, the inclusion is understood as a right. The social commitments of the Institute of Higher Education that join the program need to be translated into concrete actions of hosting, guiding and monitoring the scholarship students